Effect of Dietary Inclusion of Turmeric (Curcuma longa) and Garlic (Allium Sativum) Powders as Feed Additives on Growth Performance and Cell Mediate Immune Response of Broiler Chicken - Choudhary, Sonali; Khan, Nazam; Sharma, R. K.; Sasan, Jasvinder Singh; Mahajan, Vikas (International Journal of Bio-resource and Stress Management, 2022)
The study was conducted during 2019 at the Faculty of Veterinary Sciences & Animal Husbandry, Sher-e-Kashmir University of Agricultural Sciences & Technology-Jammu, India to investigate the effect of dietary inclusion of garlic, turmeric and their combinations on performance of broilers (Cobb strain). 240-day old unsexed broiler chicks were procured, weighed and randomly divided into 5 dietary treatments (n=48): antibiotic (C), 1% turmeric (T1), 1% garlic (T2), 0.6% turmeric±0.4% garlic (T3), 0.6% garlic±0.4% turmeric (T4) replicated 4times (12 birds / replicate). The diets formulated were isocaloric and isonitrogenous. Experimental trial lasted for 42 days. Feed consumption of broilers on weekly basis showed non-significant variation during first two weeks, but at 3rd week, feed intake was higher (p<0.05) in antibiotic growth promoter supplemented group than garlic supplemented groups. Weekly body weight and body weight gain during the entire trial did not differ except at week 1. Average weekly FCR was similar (P>0.05) throughout the experimental trial of different dietary treatments, but was numerically better in garlic fed group. Weekly PER showed no difference. Average CMI response of broiler birds was statistically higher (p<0.05) in T1 than T4 with intermediate values in C, T2 and T3 at 24 hours, indicating that turmeric has immunomodulatory properties. But, at 48 and 72 hours, there was no difference found in CMI response. The mean values of cell mediated immune response showed no significant difference. It was concluded that turmeric and garlic powder supplementation (@ 1%) either alone or in combination may substitute antibiotics without any adverse effect.